2021
DOI: 10.1021/acs.inorgchem.0c03558
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into the Dicopper-Complex-Catalyzed Hydroxylation of Methane and Benzene Using Nitric Oxide: A DFT Study

Abstract: Although hydrocarbons are known to act as reductants for the catalytic reduction of nitric oxides (NO x ) over copper-based catalysts, the reaction mechanism requires clarification. Herein, density functional theory (DFT) calculations were carried out to investigate the reduction mechanisms of NO x to dinitrogen coupled to the hydroxylation of methane or benzene using the dicopper complex reported by Zhang and co-workers [J. Am. Chem. Soc.20191411015910164]. The B3LYP functional was used to optimize the (μ-ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…A preceding PBE study for this reaction provided the overall energy change of about −38 kcal/mol, which is consistent with our result. Could one use a hybrid functional, the energy difference would get closer to the experimental enthalpy difference, but there would still be a deviation of about 10 kcal/mol from the experimental value …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A preceding PBE study for this reaction provided the overall energy change of about −38 kcal/mol, which is consistent with our result. Could one use a hybrid functional, the energy difference would get closer to the experimental enthalpy difference, but there would still be a deviation of about 10 kcal/mol from the experimental value …”
Section: Resultsmentioning
confidence: 97%
“…Could one use a hybrid functional, the energy difference would get closer to the experimental enthalpy difference, but there would still be a deviation of about 10 kcal/mol from the experimental value. 77 3.6. Comparison with IrO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…These doublet/quartet splitting energies are much smaller compared to those predicted by DFT. 32 However, they are still higher than the experimental values, perhaps due to the solid-state or solution environment of the [ H LCu 2 (O)(NO)] 2+ structure, zero-point vibrational effects, and approximations in the SC-NEVPT2/SA-CASSCF method. Analysis of the SA-CASSCF spin density for the S = 1/2 and S = 3/2 states shows that the unpaired electron is localized on the bridging oxo ligand (Figure 4).…”
Section: ■ Introductionmentioning
confidence: 89%
“…However, a recent computational study by Yoshizawa and Shiota proposed an alternative S = 3/2 state for the [ H LCu 2 (O)(NO)] 2+ complex. 32 Encouraged by their work, we further examined the EPR of [ H LCu 2 (O)(NO)] 2+ at low temperature (5 K) and high microwave power (2.0 mW) and observed an S = 3/2 signal at g = 1.95. Spectral simulation of the S = 3/2 signal allowed us to determine zero-field splitting parameters of D = 0.2 cm −1 and E/D = 0.3 (Figure 2, red).…”
Section: ■ Introductionmentioning
confidence: 99%
“…In evaluating the antioxidant activity of MD, one has to also consider that pyridines are very good coordinating ligands and therefore it is highly likely that MD forms chelates with trace metals [5,6]. Previous studies showed that the presence of transition metals such as Cu(I) can produce hydroxyl radicals via the Fenton-like reaction (1.1) [7][8][9][10][11]:…”
Section: Introductionmentioning
confidence: 99%